ANALYTIC STUDY ON HIGH-VOLTAGE CROWBAR SYSTEM - Campos, D. O.; Machida, M.; Honda, R. Y.; Aramaki, E. A.; Berni, L. A. (Japan J Applied Physics, 1995)
Crowbar switches are largely used in plasma devices, such as field-reversed configuration (FRC) machines and tokamaks, to avoid energy return from the discharge coil to the capacitor bank. A method of identification of all resistances, inductances and currents involved in capacitor bank discharges using a crowbar is proposed based on the derivation of the general analytical form of the coil current. This analysis can also be used for optimization of the discharge, reducing the ripple amplitude inherent in the crowbar-switched current. Fitting results of the TC-1 UNICAMP FRC device are also presented in this work.
Keywords: CROWBAR SWITCHES; CROWBAR CURRENT; CIRCUIT ANALYSIS; HIGH-VOLTAGE AND HIGH-CURRENT; THETA-PINCH